Theory and simulation of multi-GeV laser wakefield acceleration at kHz repetition rates - van de Wetering, JJ (2024)
Deploying both analytic methods and particle-in-cell (PIC) simulations, we investigate the operating regime and performance of the Plasma-Modulated Plasma Accelerator (P-MoPA) [1]. This new approach offers the potential for GeV-scale laser wakefield accelerators (LWFA) at kHz repetition rates by taking advantage of preexisting thin-disk laser technology [2–4], overcoming the < 0.1–1 Hz shot rates of contemporary LWFA systems. We derive a 3D analytic theory of the P-MoPA for the laser pulse and wakefield evolution in long (> 100 mm) pre-formed plasma channels, and benchmark our theory with particle-in-cell (PIC) simulations. We identify a self-modulational transverse mode instability (TMI) that limits the energy of the drive pulse accepted by the modulator stage of the P-MoPA, and find that our theory agrees well. This shows that the TMI is the limiting factor of the plasma modulator, but still allows multi-joule drive pulses corresponding to multi-GeV electron beams. Extended 3D non-paraxial theory in conjunction with further PIC simulations then demonstrate the viability of multi-GeV LWFA driven by these plasma-modulated pulses. Finally, we evaluate the P-MoPA for a potential application as a kHz driver for a water-window X-ray free electron laser (XFEL).